DEPRESI DALAM NOVEL THE LOVELY BONES KARYA ALICE SEBOLD - Sonambela, Ardilles A.; Sigarlaki, Stephani J.; Manus, Jeane A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â Â Â Â Â  This research entitled â€œDepresi dalam Novel The Lovely Bones arya Alice Seboldâ€ is intended as a requirement to accomplish the bachelorâ€™s degree at Faculty of Humanities Sam Ratulangi University Manado. The purposes of this research are to identify and classify the depression symptoms of Salmonâ€™s family. This research also analyzes how Salmonâ€™s families overcome their depression. This study used descriptive method in analyzing the data from the novel. The collecting data used theory of depression by Bhowmik et.al. (2012).Â  There are 15 depression symptoms from the depression theory. The results show that the Salmonâ€™s family experienced 12 depression symptoms. There are feelings of sadness, loss of interest or pleasure in normal activities, insomnia, changes in appetite, agitation, irritability or angry outbursts, slowed response, decreased concentration, tiredness or loss of energy, feelings of worthlessness or guilt, trouble in thinking, and unexplained physical problems. Jack Salmon experienced 9 symptoms, Abigail Salmon experienced 6 symptoms, and Lindsey Salmon experienced 3 symptoms. Among them experience some of the same symptoms of depression. Because the loss of Susie, they experienced depression. The Salmonâ€™s family used their own methods to deal with their depression.Keywords: Literature, The Lovely Bones, Depression, Symptoms, Social Phenomena